Crypto-Assets: Implications for financial stability, monetary policy, and payments and market infrastructures - Mehdi Manaa; Maria Teresa Chimienti; Mitsutoshi M. Adachi; Phoebus L. Athanassiou; Irina Balteanu; Alessandro Calza; Conall Devaney; Ester Diaz Fernandez; Fabian Eser; Ioannis Ganoulis; Maxime Laot; Günther Philipp; et al. (European Central Bank (ECB), 2019)
This paper summarises the outcomes of the analysis of the ECB Crypto-Assets Task Force. First, it proposes a characterisation of crypto-assets in the absence of a common definition and as a basis for the consistent analysis of this phenomenon. Second, it analyses recent developments in the crypto-assets market and unfolding links with financial markets and the economy. Finally, it assesses the potential impact of crypto-assets on monetary policy, payments and market infrastructures, and financial stability. The analysis shows that, in the current market, crypto-assets' risks or potential implications are limited and/or manageable on the basis of the existing regulatory and oversight frameworks. However, this assessment is subject to change and should not prevent the ECB from continuing to monitor crypto-assets, raise awareness and develop preparedness.
Keywords: E42; G21; G23; O33; 330; crypto-assets; characterisation; monitoring; crypto-assets risks